THE THINKING OF CONTEMPORARY ISSUES IN ISLAMIC WORLD (PEMIKIRAN ISU-ISU KONTEMPORER DALAM DUNIA KEISLAMAN) - IBNUDIN FAUZAN (Fakultas Agama Islam Universitas Wiralodra, 2019)
The article aims to explore several concept of contemporary Islamic thinking. It is the time several thinking concepts about Islam which continually developed along with social change. Islamic doctrine obligated to all humanity to learn and to use the mind. Accordingly, it created Islamic thinking concept is dynamic. Islamic religion is faith religion, worship religion, knowledge religion, and civilization religion, therefore Islamic religion received in direction of world. Islam is religion which was revelation of the god, and it is not cultural religion, however Islam is not be opposed the culture.. Islamic religion has function to guard the culture and thinking to bring the luck for humanity. In modern era, various temporary issues about Islam such a liberalism, pluralism, terrorism, and gender equity. Moeslim obligation must be rational thinking and critical thinking to respond it, therefore is not bearing anarchist and apathy society. Dialogist and openness attitude must be necessary to become main solution to solve the problems. Artikel ini bertujuan untuk menelusuri konsep-konsep pemikiran islam kontemporer. Dewasa ini konsep-konsep pemikiran tentang islam terus berkembang sesuai dengan gerak perubahan sosial. Ajaran islam mewajibkan seluruh umat manusia untuk terus belajar dan menggunakan akalnya. Hal demikianlah yang membuat konsep pemikiran islam bersifat dinamis. Agama islam adalah agama aqidah, agama ibadah, agama pengetahuian, dan agama peradaban dengan demikian islam bisa diterima diseluruh penjuru dunia. Islam adalah agama yang diwahyukan dan bukan agama budaya, namun islam tidak anti budaya. Agama islam berfungsi untuk menkawal budaya dan pemikiran agar membawa kemaslahatan bagi manusia. Pada zaman modern ini banyak sekali isu-isu temporer dalam dunia islam seperti isu liberalisme, pluralisme, terorisme, dan kesetaraan gender. Kewajiban orang islam adalah harus mampu berpikir rasional dan kritis untuk menyikapi hal demikian agar tidak melahirkan masyarakat yang anarkis dan apatis. Sikap dialogis dan terbuka sangat diperlukan bahkan menjadi solusi utama untuk memecahkan masalah tersebut.